FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU INFORMASI TERHADAP PENERIMAAN VAKSIN COVID-19 DI MASYARAKAT DESA CIARUTEUN ILIR - Mawar; Muslikhah , Febri Palupi; Ernawati , Erna (Fakultas Ilmu Dakwah dan Komunikasi, 2023)
Information behavior arises when a person is aware of the need for information used related to daily activities or work. The digital era is an era where the flow of information is growing rapidly and is easy to find. Information is so easy to create, disseminate and use by the wider community. Likewise, with the public's lack of understanding of the Covid-19 Vaccine, the public's lack of understanding of the Covid-19 Vaccine has led to community behavior regarding the rejection of the Covid-19 Vaccine by the people of Ciaruteun Ilir Village. The researcher aims to determine the information behavior of the people of Ciaruteun Ilir Village and aims to find out what factors influence the information behavior of the people of Ciaruteun Ilir Village towards the Covid-19 Vaccine. This research uses qualitative descriptive research types and methods. This research uses Wilson's (1996) theory which focuses on people's search behavior for the Covid-19 vaccine. The subjects of this research were the people of Ciaruteun Ilir Village using observation and interview data collection techniques. This research uses Miles & Huberman data analysis, the results of this research are rejection of the Covid-19 Vaccine in the Ciaruteun Ilir Village community with a lack of socialization causing the community's understanding of the importance of the Covid-19 Vaccine to not be optimal, the community's information seeking behavior process is still lacking due to psychological factors and environmental factors are factors that determine the level of success in meeting information needs.